Extracellular Vesicles Derived from Allergen Immunotherapy-Treated Mice Suppressed IL-5 Production from Group 2 Innate Lymphoid Cells - Masaya Matsuda; Seito Shimizu; Kazuyuki Kitatani; Takeshi Nabe (Pathogens, 2022)
Allergen immunotherapy (AIT), such as subcutaneous immunotherapy (SCIT), is a treatment targeting the causes of allergic diseases. The roles of extracellular vesicles (EVs), bilayer lipid membrane blebs released from all types of cells, in AIT have not been clarified. To examine the roles of EVs in SCIT, it was analyzed whether (1) EVs are phenotypically changed by treatment with SCIT, and (2) EVs derived from SCIT treatment suppress the function of group 2 innate lymphoid cells (ILC2s), which are major cells contributing to type 2 allergic inflammation. As a result, (1) expression of CD9, a canonical EV marker, was highly up-regulated by SCIT in a murine model of asthma; and (2) IL-5 production from ILC2s in vitro was significantly decreased by the addition of serum EVs derived from SCIT-treated but not non-SCIT-treated mice. In conclusion, it was indicated that EVs were transformed by SCIT, changing to a suppressive phenotype of type 2 allergic inflammation.